2022
DOI: 10.3389/fcvm.2022.913156
|View full text |Cite
|
Sign up to set email alerts
|

Fibulin-3 Deficiency Protects Against Myocardial Injury Following Ischaemia/ Reperfusion in in vitro Cardiac Spheroids

Abstract: Myocardial infarction (MI, or heart attack) is a leading cause of death worldwide. Myocardial ischaemia reperfusion (I/R) injury typical of MI events is also associated with the development of cardiac fibrosis and heart failure in patients. Fibulin-3 is an extracellular matrix component that plays a role in regulating MI response in the heart. In this study, we generated and compared in vitro cardiac spheroids (CSs) from wild type (WT) and fibulin-3 knockout (Fib-3 KO) mice. These were then exposed to pathophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…On the other hand, several inflammatory genes including Ccl3 and Il1r2 were upregulated in Efemp1 −/− infarct zone tissue (and were top/key components in enrichment of many identified pathways), suggesting that an overstimulation in leukocyte infiltration and inflammatory pathway activation may have also significantly contributed to the underlying mechanisms of Efemp1 −/− cardiac rupture. This is in support of a recent organoid study by Sharma et al (2022), in which we showed that there was differential expression between Efemp1 −/− and WT cardiac spheroids after ischaemia/reperfusion injury, including an upregulation of Mmp13 and Ccl2 and Ccl11 35 . Interestingly, this study also showed that control, non-infarcted Efemp1 −/− cardiac spheroids demonstrated decreased expression in fibrotic genes Col1a1 , Ctgf , Dcn and Fn1 , with an increase in Col1a1 and F2r compared to WTs.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, several inflammatory genes including Ccl3 and Il1r2 were upregulated in Efemp1 −/− infarct zone tissue (and were top/key components in enrichment of many identified pathways), suggesting that an overstimulation in leukocyte infiltration and inflammatory pathway activation may have also significantly contributed to the underlying mechanisms of Efemp1 −/− cardiac rupture. This is in support of a recent organoid study by Sharma et al (2022), in which we showed that there was differential expression between Efemp1 −/− and WT cardiac spheroids after ischaemia/reperfusion injury, including an upregulation of Mmp13 and Ccl2 and Ccl11 35 . Interestingly, this study also showed that control, non-infarcted Efemp1 −/− cardiac spheroids demonstrated decreased expression in fibrotic genes Col1a1 , Ctgf , Dcn and Fn1 , with an increase in Col1a1 and F2r compared to WTs.…”
Section: Discussionsupporting
confidence: 92%
“…Taken together, NT-proBNP remains the most predictive biomarker of secondary MACE and HF in this study. However, a combination of two ECM proteins (EFEMP1 and FSTL3) and E/ e' proved to be powerful predictors of MACE and HF risk, and both protein markers can be explored as potential therapeutic targets in post-MI patients given the emerging evidence (27)(28)(29)(30).…”
Section: Predictive Performance Of Subnetwork Signatures In Immaculat...mentioning
confidence: 99%
“…The common downregulated genes show that microgravity affected the extracellular matrix regulation, including the aforementioned downregulated gene LIMA1 which is involved in focal adhesion while EFEMP1 (EGF containing fibulin extracellular matrix protein 1) encodes Fibulin-3, an extracellular matrix glycoprotein. A deficiency of Fibulin-3 was recently shown to protect cardiac spheroids against cardiac fibrosis and improving their vascular network 37 . Other downregulated genes are involved in cell senescence and apoptosis, like TKT (Transketolase) which promotes cardiomyocyte apoptosis via the cleaved Parp1/Aif pathway 38 and DNA-damage inducible transcript 3 ( DDIT3 ) which is involved in endoplasmic reticulum protein processing and plays a role in cardiomyocyte senescence 39 .…”
Section: Resultsmentioning
confidence: 99%